Not enough breast milk? Why? - Bag, Toshibananda; Saha, Mousumi; Saha, Manish (Indian Journal of Child Health, 2020)
Background: The World Health Organization (WHO) recommends exclusive breastfeeding (EBF) up to the age of 6 months for its well-known beneficial effects. Objectives: The objectives of the study were to know the profile of cases wherein the complaint of not enough breast milk exists, to find out the causes of such problem, and to find out the areas to be addressed in breastfeeding education programs. Materials and Methods: Data were collected from infants up to 180 days of age, not exclusively breastfed, attending a private clinic from April 2015 to March 2020. Very low birth weight babies and those with anatomical problems interfering with breastfeeding were excluded. Mothers were interviewed, infants examined, and breastfeeding observed for some time to find out the problems. Results: Out of total 940 infants, 63.51% had excessive cry only, 3.19% had only unsatisfactory fullness of abdomen following a feed, and 1.38% a combination of these leading to presumed insufficient breast milk. Another 12.13% of infants had difficulty suckling, mostly because of improper attachment to breast (43.86%) and lack of mother’s patience and motivation (40.35%). A good number (9.47%) of infants did not have any breastfeeding problem at all. Conclusion: Excessively crying infant is usually not because of inadequate breast milk. Refusal to suck is due to improper attachment, lack of motivation, or improper mother-baby bonding. These issues including the WHO recommended idea of EBF need to be addressed in different health education and breastfeeding education programs.